Do Maternal Self-Criticism and Symptoms of Postpartum Depression and Anxiety Mediate the Effect of History of Depression and Anxiety Symptoms on Mother-Infant Bonding? Parallel–Serial Mediation Models - Beato, Ana Filipa; Albuquerque, Sara; Kömürcü Akik, Burcu; Costa, Leonor Pereira da; Salvador, Ágata (Frontiers in Psychology, 2022)
History of depression, including before and during pregnancy, has been identified as an important risk factor for postpartum depression (PPD). This condition has also been associated with diverse implications, namely on the quality of mother-infant bonding. Plus, the role of self-criticism on PPD has been recently found in several studies. However, the link between these factors has not been explored yet. Further, anxiety in postpartum has been less studied. Methods: This study analyzed if the history of depression predicted mother-infant bonding, via self-criticism and depression symptoms. The same model was repeated with history of anxiety and present anxiety symptoms. Participated in this cross-sectional study 550 mothers of infants less than 24 months old, who answered an online survey. Results: Through a parallel serial mediation model, results show that in a first stage, self-criticism dimensions of inadequate-self, hated-self and reassuring-self, and in a second stage, postpartum depression, mediate the relationship between history of depression and mother-infant bonding. However, the relationship between history of anxiety and mother-infant bonding is not mediated by the considered chain of mediators, neither related to self-criticism or to postpartum anxiety. Conclusion: The current study confirmed the association of history of both depression and anxiety with mother-child bonding as well as the roles of self-criticism and postpartum depressive and anxious symptoms as mediators of this relation. The buffering effect of self-reassuring on bonding and on negative affect was also evidenced. Psychological and preventive interventions should address these evidence to target interventions for bonding problems in accordance with previous and present maternal risk factors.